Paradigma dan efektivitas Mahasiswa UINSI dalam membantu memajukan desa Bunga Putih - Hudriansyah, Hudriansyah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2022)
UINSI has developed KKN activities including a series of interdisciplinary integrative activities that are strategically packaged to solve problems completely and carried out with the community by playing the community as an important and main actor and involving other relevant stakeholders. We raised the title of the activity